2012
DOI: 10.7241/ourd.20123.38
|View full text |Cite
|
Sign up to set email alerts
|

A study of nail changes in various dermatosis in Punjab, India

Abstract: Nails act as a window to diagnosis of skin diseases. Various dermatosis affect the nails and the severity of the skin disorder is reflected in the nails. Nail changes are seen in various dermatosis like psoriasis, lichen planus, onychomycosis, collagen vascular disorders, vescicobullous disorders and other papulosquamous disorders. We will discuss in detail regarding nail changes in various dermatosis. StreszczeniePaznokcie są jak okno w diagnostyce chorób skóry. Różne dermatozy wpływają na paznokcie a ciężkoś… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
12
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 23 publications
(20 reference statements)
14
12
4
Order By: Relevance
“…In our study most of the patients (25.4%) were seen in the age group of 30-40 years followed by the patients in the age group of 20-30 years. These findings were similar to the study conducted by Puri N et al 9 who observed that the maximum number of patients with nail changes (40%) were in the age group of 21-40 years.…”
Section: Discussionsupporting
confidence: 92%
“…In our study most of the patients (25.4%) were seen in the age group of 30-40 years followed by the patients in the age group of 20-30 years. These findings were similar to the study conducted by Puri N et al 9 who observed that the maximum number of patients with nail changes (40%) were in the age group of 21-40 years.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, many diseases share similar changes, but correlation of the nail changes helps dermatologist to reach conclusive diagnosis. 24 Biopsy of the nail unit is recommended in many cases when the diagnosis is in doubt or when definitive histopathologic diagnosis is needed before beginning therapy. 25 In our study, histopathologic picture was evident and aid in the diagnosis of various nail changes of aging (as onychorrhexis, onycholysis, and atrophy) and nail disorders (as psoriasis, lichen planus, and lichen simlex chronicus).…”
Section: Discussionmentioning
confidence: 99%
“…Both fingernails and toenails are vulnerable to the infection. According to previous reviews, Onychomycosis is the most common nail disease which represents about 50% of all nail changes and for about 30% of all cutaneous fungal infections [2][3][4][5][6]. Nail infections usually exhibits itself as discoloration and thickening of the nail and crumbling edges.…”
Section: Introductionmentioning
confidence: 99%
“…Nail infections usually exhibits itself as discoloration and thickening of the nail and crumbling edges. The latter manifest itself mostly in toenails [5,6]. Nail infection like onychomycosis is responsible for almost half of all nail disorders and one third of cutaneous fungal infections [5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation